(untitled) ("Conference on Universal Science Research 2023", 2023)
Human beings have cultivated pomegranate (Punica granatum L.) for its medicinal and nutritious properties for over 4000 years. Pomegranate fruit with 2.5–three million tons of annual global production is used to manufacture a wide range of food products such as fruit juice, concentrate, anardana, jam, candies, toppings, and canned arils besides its fresh consumption